Two new species of the genus Melanotus Eschscholtz (Coleoptera: Elateridae; Melanotinae) from Pakistan - Akhter, Muhammad Atique; Platia, Giuseppe; Rizvi, Syed Anser; Ahmed, Zubair (Zootaxa, 2011)
Two new species, Melanotus kalamensis and M. usrae are described from Kalam, Swat Valley, Pakistan and compared with closely allied species. Male genitalia of both new species are illustrated and a key to all known species of the Genus Melanotus from Pakistan is provided. The total number of species in the genus Melanotus from Pakistan is 18.